Immune Control Despite Protracted Lymphopenia After Chemoradiation in an Elite Controller. (29th January 2016) - Reiss, Kim A.; Jackson, Dvone C.; Piotrowski, Anna; Grossman, Stuart; Blankson, Joel N.
Abstract: Elite controllers are human immunodeficiency virus-1–positive individuals capable of sustaining undetectable viral loads without treatment. We present the case of an elite controller diagnosed with extensive stage small cell lung cancer who maintained a viral load of <20 copies/mL despite the development of severe treatment-related lymphopenia.